Pregabalin induced Amnesia – ACase Report - AP, Ravinandan; A, Ramesh (Indian Journal of Pharmacy Practice)
This is a case of 74 year old male patient with memory loss. The patient is a known case of type 2 diabetes mellitus, hypertension. He was recently diagnosed to have herpetic neuralgia and treated with Pregabalin 75 mg and Methylcobalamine 750 µg to control his neuropathic pain. After 2 months of treatment, patient's wife observed symptoms of forgetfulness in the patient such as keeping his belongings in one place and searching in other place. Immediately she reported to the doctor about this observation. Causality assessment of the event with WHO and Naranjo' scales suggest “Possible”. However, exact mechanism of pregabalin induced amnesia is unclear. Severity of this reaction was at level-3 as per modified Hartwig and Siegel scale. This reaction found predictable, but not preventable in nature.
Keywords: Pregabalin; Memory loss; Herpetic neuralgia